Creación de nuevos municipios en México. Procesos y perspectivas - Preciado Coronado, Jaime (Frontera Norte, 2017)
Hirineo Martínez Barragán, Luis Ramírez Sevilla†, Héctor Raúl Solís Gadea y M. Basilia Valenzuela Guadalajara, Universidad de Guadalajara, 2007